Nature and Sanctioning of White Collar Crime, 1976-1978: Federal Judicial Districts - Wheeler, Stanton ([Verlag nicht ermittelbar], 1989)
This data collection, one of only a small number available on federal white collar crimes, focuses on white collar criminals and the nature of their offenses. The data contain information on the source of conviction, offense category, number of counts in the indictment, maximum prison time and maximum fine associated with the offense, the duration and geographic spread of the offense, number of participants, number of persons arrested, number of businesses indicted, and spouse's employment. The data are limited to crimes committed solely by convicted individuals and do not include defendants that are organizations or groups. The defendant's socioeconomic status is measured using the Duncan Index. Further information provided about the defendant includes age, sex, marital status, past criminal history, neighborhood environment, education, and employment history.